Genetic and Molecular Characterization of Avian Influenza A(H9N2) Viruses from Live Bird Markets (LBM) in Senegal - Mamadou Malado Jallow; Moussa Moise Diagne; Marie Henriette Dior Ndione; Mamadou Aliou Barry; Ndiendé Koba Ndiaye; Davy Evrard Kiori; Marie Pedapa Mendy; Déborah Goudiaby; Gamou Fall; Malick Fall; Ndongo Dia (Viruses)
Despite extensive experience with influenza surveillance in humans in Senegal, there is limited knowledge about the actual situation and genetic diversity of avian influenza viruses (AIVs) circulating in the country, hindering control measures and pandemic risk assessment. Therefore, as part of the “One Health” approach to influenza surveillance, we conducted active AIV surveillance in two live bird markets (LBMs) in Dakar to better understand the dynamics and diversity of influenza viruses in Senegal, obtain genetic profiles of circulating AIVs, and assess the risk of emergence of novel strains and their transmission to humans. Cloacal swabs from poultry and environmental samples collected weekly from the two LBMs were screened by RT-qPCR for H5, H7, and H9 AIVs. Subsequently, a subset of H9-positive samples was selected for whole sequencing. From December 2023 to October 2024, 499 samples were tested, and AIV was detected in 58.3% of them. Among these, A/H9N2 was the only subtype detected in both markets, with a detection rate of 47.7% (82/172) in Thiaroye and 35.3% (42/119) in Tilene, resulting in an overall positivity rate of 42.6% (124/291). Genome sequencing of 22 A/H9N2 isolates, including 11 poultry drinking water samples, 7 carcass wash water samples, 3 fecal samples, and 1 cloacal swab, yielded 7 complete and 15 partial genomic sequences. Phylogenetic analyses of the resulting sequences showed that the A/H9N2 isolates obtained in this study formed a monophyletic cluster and were closely related to the Senegalese human strain (A/Senegal/0243/2019) identified through the national influenza sentinel surveillance program. These strains were also closely related to the A/H9N2 viruses of the G1 lineage circulating in neighboring countries, suggesting cross-border transmission. The A/H9N2 strains carried the low pathogenicity RSSR/GLF motif at the HA cleavage site and possessed several key amino acid mutations, including HA-I155T and HA-Q226L, which are associated with human host adaptation, PB2-T105V, PB2-A661T, and PB2-A588V, which are linked to the human-to-human transmission and increased polymerase activity, NS2-T14M, NS2-M100I, NS1-I106M, NS1-V222M, NS1-E223A, NS1-I226V, NS1-E227G, and NS1-P228S, which are known to alter virulence (increased or reduced) in humans or mice, and M2-S31N, which promotes drug resistance. Seven potential N-glycosylation sites were predicted in the HA protein and six in the NA protein. The selection pressure analysis revealed that the A/H9N2 isolates were primarily under neutral evolution or purifying selection pressure. Overall, our findings highlight the potential for cross-species transmission of Senegalese A/H9N2 viruses, emphasizing the need for sustained monitoring of these viruses in both animal and human populations.